Development and experimental verification of damage controllable energy dissipation beam to column connection. (15th November 2019) - Xu, Long-He; Zhang, Ge; Xiao, Shui-Jing; Li, Zhong-Xian
Highlights: A damage controllable energy dissipation (DCED) beam to column connection is proposed. Seismic behaviors of DCED connection were verified by cyclic loading tests. DCED connection exhibits better energy dissipation compared to RC connection. DCED connection achieves damage controllability and replaceability after earthquakes. Abstract: The present study develops and experimentally verifies a new type of precast concrete beam to column connection. The proposed damage controllable energy dissipation (DCED) beam to column connection places the replaceable steel connectors with low yield point in predetermined areas of beams to achieve the aim of controllable plastic development, energy dissipation and replaceability after the earthquake. Two 1/2 scale interior beam-column connections were designed, fabricated and tested under cyclic reversed loadings, including one monolithic specimen and one precast specimen. The hysteresis curves were recorded during the test, and the seismic indicators, such as strength, stiffness and energy dissipation capacity, were determined and analyzed. Test results demonstrate that the precast DCED connection has similar strength to the monolithic specimen, exhibits stable and plump hysteretic responses, and fails in a typical flexural mode, which is consistent with the criteria of strong column and weak beam. The plastic hinges in the steel connectors greatly reduces the damage in the DCED connection core and mitigates the deterioration in global stiffness of connection, meeting the requirements of damage controllable. Additionally, the DCED connection exhibits satisfactory energy dissipation capacity and has better seismic performance. It is a viable alternative to the seismic beam to column connections of precast concrete buildings in medium and high seismic intensity regions.